Shape memory and self-healing properties of polymer-grafted Fe3O4 nanocomposites implemented with supramolecular quadruple hydrogen bonds. (20th May 2019) - Xu, Sen; Zhao, Bingjie; Adeel, Muhammad; Mei, Honggang; Li, Lei; Zheng, Sixun
Abstract: The nanocomposites based on poly( n -butyl acrylate)-grafted magnetic Fe3 O4 nanoparticles were synthesized via surface reversible addition-fragmentation chain transfer (RAFT) polymerization approach. To promote the supramolecular hydrogen bonding interactions, 2-ureido-4[1H]-pyrimidinone methyl methacrylate (UPyMA) was used as a copolymerization monomer and introduced into the nanocomposites. Transmission electron microscopy (TEM) showed that the Fe3 O4 nanoparticles (NPs) were finely dispersed in the polymer matrix. The magnetic analysis showed that the nanocomposites displayed superparamagnetic properties. After the supramolecular quadruple hydrogen bonding interactions were introduced, the nanocomposites displayed the improved thermomechanical properties as evidenced by the enhanced glass transition temperatures ( T g 's), Young's modulus and ultimate tensile mechanical strength compared to the unmodified nanocomposites. Most importantly, the nanocomposites were newly endued with the thermally-induced shape memory properties, which can alternatively triggered by the use of the photothermal effect of Fe3 O4 nanoparticles. It was found that the rates of shape recovery were increased with the content of the quadruple hydrogen bonding motif. The introduction of the supramolecular hydrogen bonding motif ( viz. 2-ureido-4[1H]-pyrimidinone, UPy) imparted the self-healing properties to the nanocomposites via the intense dynamic exchange of hydrogen bonds. The self-healing process can be accelerated by increasing the content of the hydrogen bonding motif. Graphical abstract: The influence of supramolecular hydrogen bonding interactions on the superparamagnetic and thermomechanical properties of the nanocomposites from polymer-grafted Fe3 O4 nanoparticles was investigated in this work.Image 1 Highlights: Polymer-grafted Fe3 O4 nanocomposites with quadrupled hydrogen bonds were prepared. Supramolecular hydrogen bonds were used to modulate thermomechanical properties. Supramolecular H-bonds are critical to shape memory and self-healing properties.